What timing of vaccination is potentially dangerous for children younger than 2 years?. Issue 8 (2nd August 2016) - Gras, Pauline; Bailly, Anne-Charlotte; Lagrée, Marion; Dervaux, Benoit; , the GPIP and Infovac-France partners; Martinot, Alain; Dubos, François
ABSTRACT: Vaccine-preventable diseases still occur although measured coverage rates at 2 y of age are high. The occurrence of these diseases may be explained in part by untimely, that is, late vaccination. Our objective was to identify potentially dangerous vaccination delays for each dose of each vaccine in children younger than 2 y. A 3-round Delphi process was conducted by e-mail. We recruited 37 French experts in vaccines for children: 16 from the Infovac-France group and 21 from the French study group for pediatric infectious diseases. Items were generated by a literature review for the 10 vaccine doses recommended before 2 y of age. Item reduction in round 1 and 2 and any consensus in round 3 used a 70% consensus cutoff. The mean participation rate was 79%. Delays that should not be exceeded were identified for all vaccine doses. The 70% consensus was reached for 6 of the 10 vaccine doses: 15 d after the recommended date for the first 2 doses of the diphtheria-tetanus-acellular pertussis-inactivated polio vaccine/ Haemophilus influenzae b vaccine and for the second dose of the pneumococcal conjugate vaccine, 1 month for the meningococcal C vaccine and for the first dose of the measles-mumps-rubella vaccine, and 11 y of age for completion of the hepatitis B vaccination. This Delphi process identified potentially dangerous vaccination delays for children to the age of 2 y. These can be used as new indicators in further studies of vaccine effectiveness and can help to improve the quality of vaccine protection in children.